Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Medan Selatan - Dapot Lumban Gaol; Agus Purwoko; Erika Revida (Journal on Education, 2023)
Taxpayer compliance is one of the measuring instruments for the success of motor vehicle tax revenues. This study aims to analyze the influence of economic conditions, tax sanctions and modernization of the tax administration system towards the compliance of motor vehicle taxpayers in Samsat South Medan. The theory used in this study is Risk Opposing Theory (Risk Aversion Theory). The population in this study was all motor vehicle taxpayers registered at the Samsat Joint Office in Medan Selatan with a total sample of 271 samples The sample determination technique is accidental sampling. This research is a type of quantitative research using primary data, data obtained by spreading questionnaires. Analytical techniques that Used is multiple linear regression with first a classical assumption test consisting of a normality test, a multicolenierity test, and a heteroskedasticity test. After the classical assumption test fulfilled followed by hypothesis test with t test and F test. The results showed that both partially and simultaneously the variables of the quality of economic conditions, tax sanctions, and modernization of the tax administration system positively affect to the compliance of motor vehicle taxpayers in Samsat South Medan.